A matched, real-world observational study of the burden of osteogenesis imperfecta and healthcare resource utilization in Ontario, Canada - Erru Christy Yang; Pinay Kainth; Saranya Nair; Natalie Nightingale; Sophia Rodopoulou; Andrew Howard (BMC Musculoskeletal Disorders, 2026)
Abstract Background Osteogenesis imperfecta (OI) is a rare genetic disorder characterized by bone fragility and deformity. This study aimed to estimate the incidence and prevalence of OI in Ontario, Canada, and to describe the burden of illness (BOI) among patients with OI. Methods A retrospective, population-based, matched observational study was conducted using Ontario health administrative data from ICES (formerly Institute for Clinical Evaluative Sciences). Patients with OI were identified using ICD-10-CA codes from hospital and emergency department records between January 1, 2008, and December 31, 2021. The study included an incidence and prevalence cohort and a BOI cohort, with the latter exact-matched to controls (general population without OI) on age, sex, and geography. The BOI cohort was followed for one to three years. Outcomes included OI incidence and prevalence, patient demographics, healthcare resource utilization (HCRU), direct healthcare costs, and fracture rates. Results The study identified 565 patients with OI, with a median (IQR) age of 14 (5–37) years (57% children aged 1–17) and 48% male. The annual incidence of OI ranged from 0.14 to 0.46 per 100,000, while prevalence stabilized at 3.9 per 100,000 over the study period. Fracture rates were higher among patients with OI than controls, with a mean (SD) rate of 0.7 (0.9) fractures per person per year. Rates were particularly high among children, at 0.8 (0.9) fractures per person per year. Patients with OI had significantly higher HCRU compared to controls, with greater mean numbers of specialist visits (29.1 [35.8] vs. 4.9 [12.4]), general practitioner visits (18.8 [32.1] vs. 7.6 [9.7]), emergency department visits (4.9 [10.1] vs. 1.1 [2.1]), and hospitalizations (1.7 [2.0] vs. 0.1 [0.5]) (all p < 0.001) over the follow-up period. The mean total cost (excluding Ontario Drug Benefit costs) per OI patient over the three-year follow-up was also higher than controls ($47,348 [$77,161] vs. $4,667 [$16,480]; p < 0.001). Conclusions This study provides the first real-world estimates of OI incidence and prevalence in Ontario, highlighting its significant healthcare burden, as well as the need for improved interventions to reduce fractures and associated burden and further research to improve the management and outcomes of OI patients.